Urinary Prostaglandins and the Effect of Indomethacin on Phosphate Excretion in Children With Hypophosphatemic Rickets - SEIKALY, MOUIN G. (2008)
We recently reported the urinary prostaglandin E(2)/creatinine ratio (PGE(2)/Cr) was markedly elevated in Hyp mice, the animal model for X-linked hypophosphatemia, compared with control mice. We provided evidence for altered prostaglandin production mediating the phosphaturia and that indomethacin decreases urinary phosphate excretion in Hyp mice but not control mice. To determine the levels of urinary PGE(2)/Cr, the safety and efficacy of indomethacin on phosphate excretion in children with hypophosphatemic rickets (HPR), a prospective clinical trial was performed in 16 children with HPR and 16 age- and gender-matched healthy controls. Urinary PGE(2)/Cr excretion was determined on a 24 h timed urine collection. A randomized cross over, placebo versus indomethacin, clinical trial was performed in the 16 children with HPR. There was no difference in urinary PGE(2)/Cr excretion between controls and patients with HPR. In children with HPR, indomethacin treatment for 3 mo had no significant effect on serum phosphorus or urinary phosphate excretion. In conclusion, urinary prostaglandin excretion is similar in children with HPR compared with controls. Indomethacin had no significant effect on serum phosphorus or urinary phosphate excretion in children with HPR.